The genetic drift of human papillomavirus type 16 is a means of reconstructing prehistoric viral spread and the movement of ancient human populations. - Ho, L (1993)
We have investigated the diversity of a hypervariable segment of the human papillomavirus type 16 (HPV-16) genome among 301 virus isolates that were collected from 25 different ethnic groups and geographic locations. Altogether, we distinguished 48 different variants that had diversified from one another along five phylogenetic branches. Variants from two of these branches were nearly completely confined to Africa. Variants from a third branch were the only variants identified in Europeans but occurred at lower frequency in all other ethnic groups. A fourth branch was specific for Japanese and Chinese isolates. A small fraction of all isolates from Asia and from indigenous as well as immigrant populations in the Americas formed a fifth branch. Important patterns of HPV-16 phylogeny suggested coevolution of the virus with people of the three major human races, namely, Africans, Caucasians, and East Asians. But several minor patterns are indicative of smaller bottlenecks of viral evolution and spread, which may correlate with the migration of ethnic groups in prehistoric times. The colonization of the Americas by Europeans and Africans is reflected in the composition of their HPV-16 variants. We discuss arguments that today's HPV-16 genomes represent a degree of diversity that evolved over a large time span, probably exceeding 200,000 years, from a precursor genome that may have originated in Africa. The identification of molecular variants is a powerful epidemiological and phylogenetic tool for revealing the ancient spread of papillomaviruses, whose trace through the world has not yet been completely lost.